THE ANALYSIS OF READING SPEED AND COMPREHENSION ON ENGLISH TEXTS BY THE STUDENTS OF CLASS VII B SMP NEGERI 3 MENGWI - I Gede Neil Prajamukti Wardhana (LPPM Universitas Dhyana Pura, 2016)
ABSTRACT Speed reading is not usually accompanied by good comprehension (Sutjiati Beratha, 2006).That is why an effective and efficient reading skill is needed to make balance on reading speed and comprehension. Reading is also the one of the subjects which have importantfunction in learning English. The theory used to analyze is SRA Reading Laboratory® Blue2C which are consists of Rate Builder test and Power Builder test. The first problem is to analyze the reading speed and comprehension of the students of class VII B in SMP Negeri 3 Mengwi. The second problem is to find out the objections the reading speed and comprehension of the students of class VII B in SMP Negeri 3 Mengwi. As the result of thisstudy for reading speed and comprehension of the students of class VII B in SMP Negeri 3Mengwi were under standard level from the average difficulty 200-300 words per minute for reading speed and comprehension with 70 %. Keywords: reading speed, comprehension, analyze, result ABSTRAK Kecepatan membaca biasanya tidak disertai dengan pemahaman yang baik (Sutjiati Beratha,2006). Itulah sebabnya keterampilan membaca yang efektif dan efisien diperlukan untuk membuat keseimbangan pada kecepatan membaca dan pemahaman. Membaca jugamerupakan salah satu mata pelajaran yang memiliki fungsi penting dalam belajar bahasa Inggris. Teori yang digunakan untuk menganalisis adalah SRA Reading Laboratory® Blue2C yang terdiri dari Rate Builder test dan Power Builder test. Masalah pertama adalah untuk menganalisis kecepatan membaca dan pemahaman siswa kelas VII B SMP Negeri 3Mengwi. Masalah kedua adalah untuk mengetahui keberatan kecepatan membaca danpemahaman siswa kelas VII B SMP Negeri 3 Mengwi. Sebagai hasil dari studi ini untuk kecepatan membaca dan pemahaman siswa kelas VII B SMP Negeri 3 Mengwi berada dibawah tingkat standar dari kesulitan rata-rata 200-300 kata per menit untuk kecepatan membaca dan pemahaman dengan 70%.Kata kunci: kecepatan membaca, pemahaman, analisis, hasil